Protestation et appel à la pitié : une démarche performative. Les lettres de prélats sur la déportation des juifs en 1942 - Francine Edelstein (Argumentation et Analyse du Discours, 2020)
In France, following the mass arrests and the deportation of the Jews during the summer of 1942, high dignitaries of the Catholic and Protestant Churches in the occupied zone launched an appeal to pity and expressed for the first time their indignation in the public sphere. Through the discursive and argumentative analysis of five of their letters, this contribution examines appeal to pity in its relation to protest understood as a speech act linked to an event arousing strong opposition and stirring outrage. It shows the way pity is connected to the Christian virtue of charity, but also to various other values such as justice or the right to asylum, in order to nourish a vehement moral protest. It also examines in the framework of the epistolary texts the way in which the tension between ethical protest and political positioning is managed. Indeed, the question of the responsibility of the Vichy government, to which the Church had pledged allegiance, is problematic and is dealt with differently by the different prelates.